The Effects of Exercise & Coordination Eyes-Hand against Drop Shot Accuracy in Badminton Athletes - Pardiman, Pardiman; Sugiharto, Sugiharto; Rifai RC, Achmad (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this research is to know and analyze: (1) Differences in the influence of one-way drilling drills and two-way drilling to the accuracy of the drop shot at the athletes PB C-PLUSco Semarang. (2) Differences in influence between athletes who have high and low eye-hand coordination on the accuracy of drop shot at athletes PB C-PLUSco Semarang. (3) The interaction between exercise and eye-hand coordination to the accuracy of a drop shot at athletes PB C-PLUSco Semarang. This research uses an experimental method with the 2x2 factorial design. Data analysis technique using Analysis of Varian (ANOVA) at significance level (Î±) 0.05. The independent variable in this research is the method of drilling one-way drilling and two-way drilling. High and low eye-hand coordination as attribute variable and the dependent variable is the accuracy of a drop shot. The result of this research are: (1) There is the significant difference of influence between one-way drill and two-way drilling method toward the drop shot accuracy with sig value (0.019) < Î± (0.05) and Fvalue (7.53) > Ftable (4.49), (2) There is a difference in the effect of high and low eye-hand coordination on the accuracy of drop shot where the significance value (0.042), < Î± (0.05) and Fvalue (5.25) > Ftable (4.49), (3) method of exercise and eye-hand coordination of drop shot precision with sig (0.022) < Î± (0.05) and Fvalue (6.14) > Ftable (4.49).